Pemenuhan Fasilitas Kebun Binatang Surabaya Sebagai Destinasi Wisata Ramah Anak - Simamora, Widya T L; Noviyanti, Upik Dyah Eka (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2035, 2026)
Surabaya Zoo is a tourist destination in Surabaya, serving as a center for recreation, conservation, and education. KBS, which is predominantly visited by children, is a key driver of its status as a child-friendly tourist destination. This study aims to identify various child-friendly indicators that KBS has met and propose necessary facility improvements. The research method used a qualitative approach with descriptive methods. Data were obtained through direct observation, interviews with staff and visitors, and analysis of documents related to programs and facilities. The results indicate that KBS has met several child-friendly indicators, including safe play areas, interactive educational programs, and a strict security system. However, several shortcomings remain, such as child-friendly restrooms, healthy food options, and an educational thematic museum. Recommended future facilities include the addition of special restrooms for children, the provision of healthy food menus, and the development of an interactive thematic museum. It is hoped that KBS can further strengthen its position as a child-friendly tourist destination that is not only entertaining but also educational, providing a beneficial and enjoyable experience for all children. Keywords: S urabaya Z oo, child-friendly tourist destination, tourism